Knowledge Transfer Portal For Bachelor And Master Of IT Course Students - Hawedi, Mohamed Omran Ali (2008)
In spite of the fact that the field of applying knowledge research in education is fairly young it is already quite broad and fuzzy. The set of technologies used and developed there have roots in a variety of diverse areas of information and pedagogical sciences. To facilitate the process of scientific and scholastic search the domain needs to be structured. This paper presents an overview of a knowledge transfer portal for Education field and an initial report on the development of a web portal providing a single network place, where instructors, students, and practitioners can find information about available research projects and courses and successful practices in this field.